Green Synthesis and Cosmetic Application of Silver Nanoparticles - Tuyet Nga Nguyen; Van Toan Phi; Huy Bach Phi; Thanh Thai Tran; Van Thang Pham; Cong Tu Nguyen; Thi Lan Anh Luu (My University, 2025)
Green Synthesis and Cosmetic Application of Silver Nanoparticles
Keywords: Silver nanoparticles; Green synthesis; Cosmetics